The Effectiveness of Problem-Based Learning Integrated Audio-Visual Media in Enhancing Student Learning Outcomes on the Water Cycle Topic - Dewi, I Gusti Ayu Mas Putri Shinta; Astawan, I Gede; Trisna, Gusti Ayu Putu Sukma (Universitas Pendidikan Ganesha, 2024)
The utilization of innovative learning media is a critical strategy to enhance student learning outcomes. This study aims to analyze the significant impact of problem-based learning (PBL) integrated audio-visual media on students' learning outcomes in the water cycle topic. Employing a quasi-experimental design, the research involved an experimental group of 28 students and a control group of 22 students, selected from a total population of 300 fifth-grade students. Data collection was conducted using tests to measure student learning outcomes. The data were analyzed using descriptive statistics to provide an overview of learning results and inferential statistics to test the significance of the media's effect. The findings reveal a significant influence of PBL-based audio-visual media on students' learning outcomes in the water cycle topic. These results indicate that integrating audio-visual media with a problem-based learning approach effectively enhances students' conceptual understanding compared to conventional teaching methods. In conclusion, PBL-based audio-visual media is an effective learning tool for improving student outcomes, particularly in topics requiring visual and interactive conceptual understanding. Innovation in audio-visual learning media based on problem-based learning has implications for increasing students' interest in learning because it presents interesting and challenging problems.